7D.04: ACUTE SALT LOADING AFFECTS VASCULAR FUNCTION WITHOUT SIGNIFICANT CHANGE IN BODY FLUID STATUS AND BODY COMPOSITION IN YOUNG HEALTHY WOMEN. (June 2015) - Cavka, A.; Rasic, L.; Cosic, A.; Jukic, I.; Drenjancevic, I.
Abstract : Objective: Our previous study demonstrated that one week of salt loading significantly impaired skin microvascular reactivity without changes in blood pressure (BP) levels. The aim of this study was to evaluate whether one week of high-salt (HS) diet changes body fluid status and body composition subsequently affecting vascular reactivity. Design and method: 10 healthy women (age range 20–23) took a 7-days low-salt (LS) diet (<40mmol Na/day) and 7-days HS diet (∼240mmol of Na/day). Salt resistance, defined as a <5 mmHg change in BP determined while on the LS and HS diets was confirmed in all subjects. Skin microvascular post occlusive reactive hyperemic (PORH) blood flow (indicator of endothelial function) was assessed by laser Doppler flowmetry (LDF) before and after each diet protocol. Plasma Renin Activity (PRA), plasma aldosterone, plasma and 24h-urine sodium, potassium, urea and creatinine levels were measured before and after diets. Body composition was assessed with a four-terminal portable impedance analyzer (Maltron Bioscan 920-II). Body Mass Index (BMI), Fat Free Mass% (FFM%), Fat Mass% (FM%), Total Body Water% (TBW%), Extracellular Water% (ECW%), Intracellular Water (ICW%), ECW/ICW, Plasma Fluid (PF), Interstitial Fluid (IF) and Body Density Mass (BDM) were calculated. Results: Changes in 24 h urinary sodium, PRA and plasma aldosterone levels confirmed subjects conformed to the diet. There was no change in BP and HR before and after both diet protocols. HS diet caused significant impairment in microvascular reactivity (PORH) (R-O LS diet 156 ± 23% vs. HS diet 100 ± 12%, P = 0.040). One week HS diet did not induce any significant change in body composition parameters BMI, FFM%, FM% and BDM, compared to LS diet. Body fluid components (TBW%, ECW%, ICW%, ECW/ICW, PF and IF) were not different in LS compared to HS group. Conclusions: This study confirmed that even one week of HS diet significantly altered microvascular reactivity in young healthy normotensive and salt-resistant women, without changes in BP. Furthermore, our results indicate that vascular changes after HS diet are independent of body composition and body fluid status just as they are pressure independent, but are consequence of unique effect of HS on endothelial function.